Renovation in Vietnam : (Knowledge, 2008)
The book is looking at Doi Moi in a spanning time- line and broad space, and presenting sufficient details on the roles of the various architects and players of Doi Moi. The chapters of this book express the views and opinions of respective authors and not necessarily that of the Development Reseach Club, Vietnam Association of Crafts Villages or any other institutions to which authors may be members.